Nilai Moral dan Personal Tokoh dalam Novel Anak Mata dan Nyala Api Purba Karya Okky Madasari - Ardiyanti, Devi; Sumaryoto, Sumaryoto; Suendarti, Mamik (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2024)
The research objectives are 1) To describe the moral values in the children's novel Mata and Nyala Api Purba by Okky Madasari. 2) To describe the personal values contained in the children's novel Mata dan Nyala Api Purba by Okky Madasari. The research method used in the study is descriptive qualitative method, which is a way of solving problems by collecting, analyzing, and interpreting data. The approach used in this research is formalist approach. The conclusion obtained from the research of moral and personal values in the novel Anak Mata and Nyala Api Purba by Okky Madasari is the first moral value into 3 kinds. 1) human relationship with God is not found. 2) human relationships with other humans have 13 findings. 3) human relationship with oneself has 11 findings. Second, personal values in Okky Madasari's novel Mata and Nyala Api Purba are divided into 3 types. 1) the value of emotional development has 21 findings. 2) the value of intellectual development has 25 findings. 3) the value of imagination development has 12 findings.Keywords: Moral Value, Personal Value, Children's Novel Mata dan Nyala Api Purba by Okky Madasari